A survey of the internal oral features and external morphology of Physalaemus larvae (Anura, Leptodactylidae) - Ruggeri, Joice; Weber, Luiz Norberto (Zootaxa, 2012)
There are 45 species currently described for the genus Physalaemus that are allocated into seven morphological groupsand 29 of them have their tadpoles described, of which 12 have information on their internal oral anatomy. In order to helpresolving taxonomic and systematic problems, tadpoles from this genus had their external and internal oral morphologiesstudied, described and compared. During this study, it was noticed that different terms are sometimes used to refer to thesame character and a standardized nomenclature is suggested. This study is divided into two parts. First, we describe theoral cavity anatomy of the tadpoles of Physalaemus aguirrei, P. atlanticus, P. camacan, P. cicada, P. gracilis, P. irroratus,P. maximus, P. rupestris, P. signifer and P. soaresi. Second, we present a comparison among tadpoles of these ten speciesplus the tadpoles of P. albifrons, P. angrensis, P. centralis, P. crombiei, P. cuvieri, P. henselii, P. jordanensis, P. marmora-tus, P. moreirae and P. spiniger. This study adds information on tadpoles of the genus Physalaemus that corroborates someof the species groups proposed for adult specimens, but also shows that although they have a typical pond-living externalmorphology, being very similar to one another, the oral disc and the internal oral morphologies present many features with interspecific variation that may be used to identify the specimens.